Parent-Founded Schools for the Catholic Education of Children: Considerations for Canonical Recognition in the North American Context - Creurer, Philip A. (Université Saint-Paul / Saint Paul University, 2013)
A comparative study of parental rights over education in Catholic canon law, Canadian and American civil law and international law. After analyzing the development of the law regarding parental rights, the thesis considers the current context of education in North America and the organisational structures used in the Catholic Church to found and run schools. The experience of Catholic health care institutions and Catholic higher education is also analysed in order to present a solution in canon law for parents who wish to found a school. Draft statutes are included in the appendix.
Keywords: parental rights; Catholic schools; canon law; Catholic health care; Catholic higher education; Sponsorship; school governance; juridical person; juridic person; associations of the Christian faithful; Sponsorship of Catholic health care; lay governance